ПЕРСПЕКТИВЫ И ПРАКТИКА ИСПОЛЬЗОВАНИЯ ИСКУССТВЕННОГО ИНТЕЛЛЕКТА В СИСТЕМЕ ОБРАЗОВАНИЯ - Куранбаев Жавохир Жахонгир угли; Ражапов Дилмурад Хабибулла угли (TADQIQOTLAR.UZ, 2025)
Annotation: The article discusses the prospects and practice of using artificial intelligence (AI) in the education system. The main areas of its use are described, such as personalizing learning, assessing knowledge, supporting teachers and making education accessible. The benefits, including increased student motivation, improved teaching quality and optimization of teacher time, are analyzed, as well as challenges related to ethical issues, digital inequality and the need for staff training.